2022
DOI: 10.18632/aging.204112
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic candidate signatures by systematically revealing transcriptome characteristics in lung adenocarcinoma with differing tumor microenvironment immune phenotypes

Abstract: Accumulated evidence shows that tumor microenvironment plays crucial roles in predicting clinical outcomes of lung adenocarcinoma (LUAD). The current study aimed to identify some potentially prognostic signatures by systematically revealing the transcriptome characteristics in LUADs with differing immune phenotypes. LUAD gene expression data were retrieved from the public TCGA and GEO databases, and the transcriptome characteristics were systematically revealed using a comprehensive bioinformatics method inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Subsequently, we conducted batch differential analysis, which led to the identification of FGR , PSMD14 , and ZBTB16 as differentially expressed genes exhibiting prognostic significance. Several studies have been observed that these genes are involved in the oncogenesis of LUAD ( 58 - 61 ). In addition, our analysis revealed a marked downregulation in the expression of FGR and ZBTB16 , whereas the expression of PSMD14 was significantly upregulated in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we conducted batch differential analysis, which led to the identification of FGR , PSMD14 , and ZBTB16 as differentially expressed genes exhibiting prognostic significance. Several studies have been observed that these genes are involved in the oncogenesis of LUAD ( 58 - 61 ). In addition, our analysis revealed a marked downregulation in the expression of FGR and ZBTB16 , whereas the expression of PSMD14 was significantly upregulated in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk score based on the six-gene signature was significantly correlated with immunological status of LUAD patients. It is well known that tumor immune microenvironment (TIME) plays important roles in cancer biology, and patients with differing TIME present differing immunotherapeutic responses and clinical outcomes [ 86 88 ]. Tumor immunophenotype has been gradually recognized as an independent prognostic factor to estimate the prognosis [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that tumor immune microenvironment (TIME) plays important roles in cancer biology, and patients with differing TIME present differing immunotherapeutic responses and clinical outcomes [86][87][88].…”
Section: Discussionmentioning
confidence: 99%